CHARACTERISTICS OF BENTHIC RESOURCES AT CENTRAL VIETNAM’S LAGOONS - Ngai, Phan Duc; Tuan, Vo Si; Long, Nguyen Van; Tuyen, Hua Thai; Khang, Nguyen An (Vietnam Journal of Marine Science and Technology, 2016)
Characteristics of benthic resouces at central Vietnam’s lagoons are determined by ten surveys from 2008 - 2013. The result has identified 18 benthic species that have primarily economic value including: 8 Bivalvia species, 2 Gastropoda species, 8 Crustacea species. Bivalves are dominant in benthic yield in De Gi and Thi Nai but crustaceans are dominant in benthic yield  in Nha Phu and Thuy Trieu. Benthic yield of four lagoons primarily belongs to five species including: Gari elongata (De Gi), Glauconome chinensis và Potamocorbula cf. laevis (Thi Nai), Portunus pelagicus (Nha Phu and Thuy Trieu). The majority of benthic resources are epifauna, inhabiting in tidal zone and concentrating in sandy bottom. The results of this study will provide scientific basis for researches on the food chain, food web and data for planning, zoning and appropriately exploiting fisheries resources.